Jejunal Diverticulosis Presented with Acute Abdomen and Diverticulitis Complication: A Case Report - Fidan, Nurdan (Pol J Radiol, 2015)
BACKGROUND: Jejunal diverticulosis is a rare, usually asymptomatic disease. Its incidence increases with age. If symptomatic, diverticulosis may cause life-threatening acute complications such as diverticulitis, perforation, intestinal hemorrhage and obstruction. In this report, we aimed to present a 67-year-old male patient with jejunal diverticulitis accompanying with abdominal pain and vomiting. CASE REPORT: A 67-year-old male patient complaining of epigastric pain for a week and nausea and fever for a day presented to our emergency department. Ultrasonographic examination in our clinic revealed diverticulum-like images with thickened walls adjacent to the small intestine loops, and increase in the echogenicity of the surrounding mesenteric fat tissue. Contrast-enhanced abdominal computed tomography showed multiple diverticula, thickened walls with showing contrast enhancement and adjacent jejunum in the left middle quadrant, increased density of the surrounding mesenteric fat tissue, and mesenteric lymph nodes. The patient was hospitalized by general surgery department with the diagnosis of jejunal diverticulitis. Conservative intravenous fluid administration and antibiotic therapy were initiated. Clinical symptoms regressed and the patient was discharged from hospital after 2 weeks. CONCLUSIONS: In cases of diverticulitis it should be kept in mind that in patients with advanced age and pain in the left quadrant of the abdomen, diverticular disease causing mortality and morbidity does not always originate from the colon but might also originate from the jejunum.